Interferon-λ3 as a Predictor of Survival in Hemodialysis Patients - Grzegorzewska, A E; Swiderska, M K; Warchol, W (Current molecular medicine, 2018)
IFNL4 polymorphisms are associated with circulating IFN-λ3, and higher plasma IFN-λ3 are associated with higher production of antibodies to HBV surface antigen (anti-HBs). The IFNL4 rs8099917 T allele and anti-HBs development in response to HBV vaccine are associated with better survival in hemodialysis (HD) patients. To show whether plasma IFN-λ3 is also a predictor of survival in HD patients. Plasma IFN-λ3 was measured in 135 HD patients who were followed-up for 2.6 years. Survival probability was tested using the Kaplan-Meier method and the Cox proportional hazard model. Plasma IFN-λ3 (ng/L) was 116.8 (20.4-227.5) in survivors on HD (n=89, 65.9%), 75.1 (36.0-228.8) in deceased patients (n=37, 27.4%), and 109.0 (40.0-232.7) in subjects submitted to kidney transplantation (n=9, 6.7%). IFN-λ3 was lower in deceased patients than that in all remaining patients (P=0.039) and patients who continued HD without transplantation (P=0.028). IFN-λ3 and anti-HBs titers were correlated (r=0.587, P<0.000001). Patients showing IFN-λ3 >126.1 ng/L (3rd tertile) presented better survival compared with patients with IFN-λ3 in the 1st (<73.8 ng/L, P=0.005) and 2nd (≥73.8 - <126.1 ng/L, P=0.013) tertiles. Each decrease in IFN-λ3 per 10 ng/L was associated with a hazard ratio equal to 1.076 (95%CI 1.015-1.140, P=0.013). In multivariate analysis, the independent predictors of survival were age (P=0.008), dialysis modality (P=0.038), circulating IFN-λ3 (P=0.044), and diabetic nephropathy (P=0.047), but not gender, dialysis duration prior to the study, mean arterial pressure, BMI, CRP, albumin, 25(OH)D, or anti-HBs. Circulating IFN-λ3 is a promising predictor of HD patient survival.